If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xy + -2y + 3zy = 8 Solving xy + -2y + 3yz = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. xy + -2y + 2y + 3yz = 8 + 2y Combine like terms: -2y + 2y = 0 xy + 0 + 3yz = 8 + 2y xy + 3yz = 8 + 2y Add '-3yz' to each side of the equation. xy + 3yz + -3yz = 8 + 2y + -3yz Combine like terms: 3yz + -3yz = 0 xy + 0 = 8 + 2y + -3yz xy = 8 + 2y + -3yz Divide each side by 'y'. x = 8y-1 + 2 + -3z Simplifying x = 8y-1 + 2 + -3z Reorder the terms: x = 2 + 8y-1 + -3z
| 23ab+69ab=ab(23a+69ab) | | 7y-3=20-2 | | 1/3*x^3-4*x=0 | | 4x-16y=-12 | | 19x*x-9x-100=135 | | 64x-8xy=0 | | -7(x+12)=-91 | | 50-3x=90 | | 6x+16=106 | | 4x^2+4y^2+6x+8y-5=0 | | 3*(x+12)+5x=92 | | 6x+16 = 106 | | 7.4x+17=76.2 | | -6x-8 = -50 | | 2.7x+18=63.9 | | 10x+17=177 | | -11x+17=-126 | | 2x-15 = -19 | | 25x+7=207 | | 3(2x-4)+8=6 | | 2x/3=(X-10)/4 | | 7w+14=14 | | 7w+14=4 | | 19-5x=-15 | | 11x+13=200 | | -5x+16=-54 | | 16m^2-81(m-3)(m-3)=0 | | 1+3x=-3+9x | | 3p+12=6p-24 | | 16=25 | | 5x-0.6x=7.48 | | 2.9=8.3x |